States' Compliance to International Treaties Accountability Mechanisms Pertaining to States, IOs and NGOs - Bodmer, Louis (eCahiers de l'Institut, 2022)
This research analyzes mechanisms fostering states' compliance to international treaties. It argues that a treaty accountability network surrounds states when they commit to an international covenant and that actors belonging to the network have leverage on states to hold them accountable. This study is particularly interested in the role NGOs and IOs play as actors within this network. It identifies two main ways for holding states accountable: direct and indirect. Indirect accountability is conceptualized as mechanisms where aid recipients are empowered by organizations and will henceforth hold their states accountable. This research provides a small-N case-study on the UNCRC, maps the treaty accountability network surrounding it, identifies accountability mechanisms developed by one OI (UNICEF) and one NGO (Terre des Hommes Suisse) and examines pathways used by one state (Switzerland). We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.